Verrucous Squamous Cell Cancer of the Esophagus: A Case Report - Sumera Mushtaq, Ghulam Murtaza Gondal, Kiran Fatima, Tassawar Hussain, Sumera Mushtaq, Ghulam Murtaza Gondal, Kiran Fatima, Tassawar Hussain (Journal of Rawalpindi Medical College, 2022)
Verrucous Cancer of the esophagus is basically a type of squamous cell carcinoma and is associated with a chronic inflammatory process in the lower esophagus usually secondary to gastro-esophageal reflux disease (GERD). Mostly it is a local disease process but sometimes it can invade distant structures also. We report a case is a 62-year-old female patient who presented with marked weight loss, anorexia, and difficulty to take solid food. On Upper GI endoscopy there was a warty appearing irregular mass at the mid to distal esophagus. Superficial multiple biopsies were taken but turned negative for malignancy and re-endoscopy after a few days with deep multiple biopsies revealed the diagnosis of verrucous carcinoma on histopathology. The patient was having multiple co-morbid conditions like hypertension, diabetes mellitus, and early nephropathy along with infiltration of malignancy in surrounding structures on CT scan chest. Therefore a decision was taken to place an esophageal stent by upper GI endoscopy followed by chemotherapy and radiotherapy by the oncology department. Patient symptoms were much relieved after 4 months of chemotherapy and radiotherapy and the patient is still on regular follow-up in medical OPD. Chronic inflammation due to gastritis and esophagitis is the main risk factor for verrucous carcinoma of the esophagus. Although surgery is the treatment of the choice for the local and early disease but as in our case disease was already spread palliative stenting followed by chemo-radiation is the best possible option that can be offered.